2021
DOI: 10.1007/s42452-021-04514-7
|View full text |Cite
|
Sign up to set email alerts
|

Performance of rainfall–runoff models in reproducing hydrological extremes: a case of the River Malaba sub-catchment

Abstract: Daily River Malaba flows recorded from 1999 to 2016 were modelled using seven lumped conceptual rainfall–runoff models including AWBM, SACRAMENTO, TANK, IHACRES, SIMHYD, SMAR and HMSV. Optimal parameters of each model were obtained using an automatic calibration strategy. Mismatches between observed and modelled flows were assessed using a total of nine “goodness-of-fit” metrics. Capacity of the models to reproduce historical hydrological extremes was assessed through comparison of amplitude–duration–frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
(112 reference statements)
0
8
0
Order By: Relevance
“…The inversed distance weighed (IDW) interpolation approach (Shepard, 1968) was adopted to fill-in the missing precipitation records. The suitability of IDW interpolation for the precipitation over the study area was recently demonstrated by Chelangat and Abebe (2021) and Mubialiwo et al (2021a).…”
Section: Precipitationmentioning
confidence: 84%
See 3 more Smart Citations
“…The inversed distance weighed (IDW) interpolation approach (Shepard, 1968) was adopted to fill-in the missing precipitation records. The suitability of IDW interpolation for the precipitation over the study area was recently demonstrated by Chelangat and Abebe (2021) and Mubialiwo et al (2021a).…”
Section: Precipitationmentioning
confidence: 84%
“…The suitability of IDW interpolation for the precipitation over the study area was recently demonstrated by Chelangat and Abebe (2021) and Mubialiwo et al . (2021a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Simulated daily rainfall-runoff was adopted from the earlier study (Mubialiwo et al 2021b). The series covered the period 1999-2016 totalling to 18 years.…”
Section: Flow Data and Processingmentioning
confidence: 99%